2016
DOI: 10.3389/fpls.2016.00590
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Resistance to Broomrape (Orobanche cumana) Is Controlled by Specific QTLs for Different Parasitism Stages

Abstract: Orobanche cumana (sunflower broomrape) is an obligatory and non-photosynthetic root parasitic plant that specifically infects the sunflower. It is located in Europe and in Asia, where it can cause yield losses of over 80%. More aggressive races have evolved, mainly around the Black Sea, and broomrape can rapidly spread to new areas. Breeding for resistance seems to be the most efficient and sustainable approach to control broomrape infestation. In our study, we used a population of 101 recombinant inbred lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 60 publications
5
72
1
Order By: Relevance
“…Current findings support the reported allelopathic influence of rice on the seed germination of sunflower broomrape and clover broomrape [27]. The sunflower and Egyptian broomrape seeds may contain receptors specifically designed to receive biochemical signals and respond to it depending on the perception [31,32]. Chemical interaction may not entirely be entitled to demonstrate this situation as the possible contribution of certain physical factors, such as seed coat structure, which can alter the reception and perception of a certain biochemical or stimulus.…”
Section: The Differential Germination Indicates a Genetic And Biochemsupporting
confidence: 74%
“…Current findings support the reported allelopathic influence of rice on the seed germination of sunflower broomrape and clover broomrape [27]. The sunflower and Egyptian broomrape seeds may contain receptors specifically designed to receive biochemical signals and respond to it depending on the perception [31,32]. Chemical interaction may not entirely be entitled to demonstrate this situation as the possible contribution of certain physical factors, such as seed coat structure, which can alter the reception and perception of a certain biochemical or stimulus.…”
Section: The Differential Germination Indicates a Genetic And Biochemsupporting
confidence: 74%
“…Post‐haustorial mechanisms operate after vascular connections between broomrape and its sunflower host have been established and nodules are visible (Pérez de Luque et al., 2009). Necrosis and subsequent death of broomrape nodules at several stages of development have been reported in sunflower line LR1 (Labrousse et al., 2001; Louarn et al., 2016; Zélicourt et al., 2007). Louarn et al.…”
Section: Introductionmentioning
confidence: 94%
“…This procedure allowed the authors to detect genes with consistent differential expression over the three growing seasons, thus uncovering genes underlying general soybean responses to weed presence. Four of the five remaining studies reported phenotyping experiments in both controlled and field conditions (Schmidt and Baldwin, 2006;Fondevilla et al, 2010;Horvath et al, 2015;Louarn et al, 2016). While controlled and field conditions are complementary, natural selection acts in nature, where the neighbor plants and associated cues are numerous and complex.…”
Section: Highlights On the Nature Of The Datamentioning
confidence: 99%